2015
DOI: 10.1016/j.cell.2015.04.053
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Gene Regulatory Network Resets the Human Germline Epigenome for Development

Abstract: SummaryResetting of the epigenome in human primordial germ cells (hPGCs) is critical for development. We show that the transcriptional program of hPGCs is distinct from that in mice, with co-expression of somatic specifiers and naive pluripotency genes TFCP2L1 and KLF4. This unique gene regulatory network, established by SOX17 and BLIMP1, drives comprehensive germline DNA demethylation by repressing DNA methylation pathways and activating TET-mediated hydroxymethylation. Base-resolution methylome analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
748
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 576 publications
(812 citation statements)
references
References 40 publications
56
748
2
6
Order By: Relevance
“…Shortly after conception, when the first cell divisions are taking place, the stem cells are generally cleared of all methylation (Farooq, 2010, Mayer et al, 2000. However, recent evidence suggests that some loci associated with metabolic and neurological disorders are also resistant to DNA demethylation (Tang et al, 2015). If epigenetic modifications take place on the part of the genome that is genetically imprinted, this could explain sex-specific epigenetic inheritance.…”
Section: Epigenetic Imprintingmentioning
confidence: 99%
“…Shortly after conception, when the first cell divisions are taking place, the stem cells are generally cleared of all methylation (Farooq, 2010, Mayer et al, 2000. However, recent evidence suggests that some loci associated with metabolic and neurological disorders are also resistant to DNA demethylation (Tang et al, 2015). If epigenetic modifications take place on the part of the genome that is genetically imprinted, this could explain sex-specific epigenetic inheritance.…”
Section: Epigenetic Imprintingmentioning
confidence: 99%
“…Here, the arriving PGCs not only maintain expression of the pluripotency genes, but also retain expression of SOX17, PRDM1 and PRMT5 (Eckert et al 2008). Recent data indicate that in humans, SOX17 is a critical determinant of PGC fate transactivating expression of PRDM1 (Irie et al 2015). In turn, PRDM1 and PRMT5 proteins cooperate to establish a symmetric dimethylation at arginine 3 of histones H2a and H4 (H2a/H4R3me2s), leading to suppression of somatic differentiation (Ohinata et al 2005, Ancelin et al 2006.…”
Section: Type I and Type Ii Gcts: Results Of A Flawed Licensingmentioning
confidence: 99%
“…Further, PRDM14, which is essential for murine PGC maintenance, shows only low levels of expression in human PGC-like cells and seminomatous TCam-2 cells, which also share a similar gene expression profile with PGCs (Irie et al 2015, Nettersheim et al 2015, Sugawa et al 2015, Tang et al 2015.…”
Section: Normal Germ Cell Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, three groups independently reported genome-wide DNA methylation and transcription profiles of hPGCs obtained from aborted embryos at the stages of arrival of the hPGCs to-and proliferation/differentiation within-the genital ridges (corresponding to E9.5-E13.5 in mice) (Gkountela et al 2015;Guo et al 2015;Tang et al 2015), and revealed fundamental similarities in epigenome reprogramming between humans and mice. These discoveries have posed several critical challenges for the future.…”
Section: Perspectivementioning
confidence: 99%